Effect of Environmental Parameters on the Reproduction of the White Mullet (Mugil curema, Valenciennes, 1836) in the Saloum Delta (Senegal) - Ndiaye, Waly; Ndiaye, Khady; Sarr, Alassane; Diédhiou, Patrick (Journal of Biology and Life Science, 2022)
Mugil curema, known as white mullet, was one of the fish species encountered in the fisheries landings of the Saloum Delta. In this study, the morphometric parameters and the reproductive biology of this species were studied as well as the influence of environmental parameters on its reproduction. Experimental fisheries were carried out monthly in the Saloum Delta. The fish were caught using surface drift nets. The captured individuals were measured and weighed. The gonads were collected to determine the sex and the stages of sexual maturity. Out of a total of 406 individuals sampled in the Saloum Delta, 306 females and 100 males were identified, no individuals of undetermined sex were obtained. The sex ratio was globally in favor of females. Individuals in this study ranged in size from 102 to 385 mm and weight from 34.9 to 395 g. The allometric coefficient b was equal to 2.40 and indicated a negative allometry. The exploitation of the monthly IGS results indicated that reproduction was in April, May and June. The size at first sexual maturity indicated that the males matured at a size of 220 mm, lower than that of the females 226 mm.